Keep on Rolling Under the Stars Green Readings on the Beat Generation - Weidner, Chad (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Beat Studies represent a vibrant field of intellectual inquiry, and this collection examines Beat culture as deeply infused with ecological themes. Allen Ginsberg invented the term "Flower Power" and Beat texts uncover the sources of our current existential climate predicament. This is the first edited collection to place the Beat Generation in conversation with the environment. A diverse number of contributors from Asia, Europe, and North America addresses essential environmental subjects and the deep ecological vision of the Beats.